Perancangan Presensi Online Menggunakan Foto Dan Geolocation Guna Meningkatkan Kedisiplinan Pegawai Berbasis Website ( Studi Kasus: PT. A Logistic International ) - Turmudi, Imam; Rosyani, Perani (Shofanah Media Berkah, 2023)
PT. A Logistic International is a company engaged in expor and impor shipping services since 2012. Work activities outside the office cause employees to forgot to take attendance, there is damage and loss when recapitulating attendance data manually and the difficulty of doing attendance remotely. The purpose of this problem is to be able to help attendance results automatically and efficiently through the website and speed up the process of recording employee attendance reports and implementing online attendance results so that they can be used when working outside the office. System Development Life Cycle (SDLC) method or called the system development of systems that are made so that they can complate the manufacturing process effectively. Through web based online attendance and using Photo and Geolocation features can make it easier for employees when taking attendance outside the office more efficient, more disciplined and reduce the risk of damage and loss of attendance data. Over time this online presence can become a habit among employees in order to creat a more dynamic presence system and can be developed for the better.